2009
DOI: 10.1149/1.3098977
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Surface and Gate-Engineered AlGaAs∕InGaAs Pseudomorphic High-Electron Mobility Transistors

Abstract: The epilayers in pseudomorphic high-electron mobility transistor ͑pHEMT͒ structures are grown by metallorganic chemical vapor deposition on GaAs substrates. A treatment with ammonium polysulfide ͑NH 4 ͒ 2 S X to passivate the surface of AlGaAs barrier layer is performed. Then, the surface morphology of the sulfur-treated AlGaAs layers was investigated by atomic force microscopy. The chemical compositions of AlGaAs surfaces before and after S treatment are studied using X-ray photoelectron spectroscopy. Two met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Through the surface passivation and Schottky gate metals engineering, the device characteristics and thermal stability can be improved. Additionally, passivation of heterojunction bipolar transistors (HBTs) [6] and heterostructure field-effect transistors (HFETs) [7,8,9,10] has been investigated. However, the comparison of GaN-based HEMTs with surface treatments before and after gate metal deposition has not yet to be exploited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the surface passivation and Schottky gate metals engineering, the device characteristics and thermal stability can be improved. Additionally, passivation of heterojunction bipolar transistors (HBTs) [6] and heterostructure field-effect transistors (HFETs) [7,8,9,10] has been investigated. However, the comparison of GaN-based HEMTs with surface treatments before and after gate metal deposition has not yet to be exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Transistors with high-temperature characteristics and excellent thermal stability are important for high frequency and high power applications. Many research groups have reported on the high-temperature performance of the GaAs-based HEMTs [7,8,9,11]. Nevertheless, little attention has been devoted to investigating the thermal stability of GaN-based HEMTs.…”
Section: Introductionmentioning
confidence: 99%
“…One solution is to passivate the surface, enabling GaN-based HEMTs to perform at high power and high frequency. An extensive amount of literature elucidates several methods of passivating compound semiconductors [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Among the various materials for passivation that have been examined, SiN X is the most commonly used passivation dielectric for AlGaN/GaN HEMTs.…”
Section: Introductionmentioning
confidence: 99%
“…Much research effort has been devoted to stimulating various compound semiconductor-based high-electronmobility transistors (HEMTs) [1][2][3][4][5][6][7] for millimeter-wave integrated circuit (MMIC) applications because of their high carrier transport and high concentration of two-dimensional electron gas (2DEG) in the narrow-gap conduction channel. However, it is known that the gate leakages are crucial to the device performance [8], including breakdown voltage, voltage gain, RF characteristics, noise figure, power amplification and high temperature reliability.…”
Section: Introductionmentioning
confidence: 99%